The Relationship between Socioeconomic Status and Consumption Pattern of Fishermen Household in Indonesia - Rusdiana , A; Sanuri; Subandi , Muhammad; Mulyawan, Setia (Asian Journal of Agriculture and Rural Development, 2020)
The purpose of this study is to analyze the relationship between socioeconomic status and consumption patterns of fishermen households in Karangsong Village, Indramayu Regency West Java Indonesia. The importance of this paper comes from the phenomenon of the lifestyle of the fishermen community who is known in general for their very harsh character. This is because their lifestyle is very dependent on nature. Even though in certain seasons fishermen's income will grow very high but in the following seasons, fishermen's income will decrease or even will be not existent. This is what causes fishermen are in the low level of social class. For this purpose, a survey was conducted to 81 fishermen during the month of August to September in 2019. Data was collected according to simple descriptive or multivariate statistical analyzes as well as qualitative techniques. The results of this study indicate that the income and number of family members influence the consumption patterns of fishermen households. It also can be concluded that there is a positive and significant impact between the independent variables (income, number of family members and education), on the consumption patterns of fishermen households.